Mortality in COVID-19 patients with renal failure and need for dialysis. An evaluative review - Meneses-Liendo, Victor Hugo (2024)
Objectives: To compare mortality in patients with COVID-19 and renal failure and need for hemodialysis from a general hospital in Lima, Peru and data from the world literature, and according to geographic areas in the world. Methods: Secondary research: evaluative review. PubMed was the database used for the bibliographic search. The keywords “renal failure”, “COVID 19” and “mortality” were used and the filters meta-analysis and systematic reviews. Thirteen articles were included. Results: The frequency of acute renal failure (AKI) and COVID-19 ranged between 8.4 and 26% and in Lima, Peru it was 22.6%; the hemodialysis (HD) rates in patients with COVID-19 was 2.97%, continuous renal replacement therapy (CRRT) was reported in AKI: Asia 1.4%, Europe 5.7% and North America 4.0% and in Lima, Peru 44.1% had CKD V on HD and 12.9% received HD for the first time (ARF 9.7% and CKD 3.2%); the OR for mortality in patients with COVID-19 and AKI ranged from 11.05 to 23.9 and mortality in patients with COVID-19 and ARF was in Asia 33.3%, Europe 29.4%, North America 7.4% and in Lima, Peru 81% (66.7% without HD and 100% with HD); in Lima, Peru, 33.3% had CKD, with an overall mortality of 23.7% (15.5% without HD and 100% with HD), and 44.1% had CKD V on HD with a mortality of 16.3%. Conclusion: Mortality in patients with COVID-19 and acute kidney failure and hemodialysis in Lima, Peru was higher compared to data in the world literature.